2021
DOI: 10.1111/ijcp.14137
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide release during exercise in patients with valvular heart disease: A systematic review

Abstract: Aim: Serum biomarkers have a potential role in the risk stratification of patients with heart valve disease and may help determine the optimal timing of intervention. Much of the published literature relates to biomarker sampling in a resting state, but the relationship of exercise biomarkers is less well described. We performed a systematic review to examine the significance of exercise natriuretic peptides on echocardiographic variables and cardiovascular events, in valvular heart disease. Methods:A search f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…Finally, natriuretic peptides are the most widely used markers of cardiac volume overload in daily clinical practice. Their application in the assessment of patients with valvular heart disease is emerging, and many studies have shown a strong correlation between natriuretic peptides and clinical outcomes in patients with symptomatic and asymptomatic MR [ 40 , 41 ]. Although specific cut-offs have not yet been defined, they can be another useful tool for implementing the management of patients with MR when indication for intervention is not clear.…”
Section: Morphology and Imagingmentioning
confidence: 99%
“…Finally, natriuretic peptides are the most widely used markers of cardiac volume overload in daily clinical practice. Their application in the assessment of patients with valvular heart disease is emerging, and many studies have shown a strong correlation between natriuretic peptides and clinical outcomes in patients with symptomatic and asymptomatic MR [ 40 , 41 ]. Although specific cut-offs have not yet been defined, they can be another useful tool for implementing the management of patients with MR when indication for intervention is not clear.…”
Section: Morphology and Imagingmentioning
confidence: 99%
“…This is explained further in the specific sections and particularly concerns HFpEF. Also, in heart valve disease, biomarkers could play a role in the stratification of patients’ risk and help identify the optimal time of cardiac surgery by identifying the early stages of HF and avoiding further structural alteration [ 19 ]. Other biomarkers evaluated as predictors of adverse outcomes are galectin-3, growth differentiation factor 15, mid-regional pro-adrenomedullin, and markers of renal dysfunction.…”
Section: Biomarkers: Historical Reviews State Of Art and New Frontiersmentioning
confidence: 99%
“…The knowledge of the effects and mechanisms of action of NPs is fundamental to investigating the electrophysiological consequences, certainly less studied, but which could prove significant considering the increase in electrical conduction and heart rate and, therefore, in oxygen consumption induced by the activation of NPR-A and NPR-B receptors and by the inhibition of phosphodiesterase 3 (PDE3) [ 43 ]. Also, in heart valve disease, the diastolic stretching that occurs following blood regurgitation in mitral and aortic insufficiency and the pressure overload typical of aortic stenosis determine the production of BNP, expression of cardiac decompensation and could independently identify individuals more at risk of cardiac events, therefore deserving of closer follow-up and any further cardiological investigations [ 19 , 44 ]. The increasing importance of NPs in the diagnosis, management, severity, and prognostic implications of HF has recently been the subject of great attention by the major scientific societies concerned with HF—Heart Failure Association of the European Society of Cardiology, Heart Failure Society of America and Japanese Heart Failure Society—in the actions of the so-called Trilateral Cooperation Project [ 45 ].…”
Section: Biomarkers: Historical Reviews State Of Art and New Frontiersmentioning
confidence: 99%
“…Например, повышается уровень циркулирующих провоспалительных цитокинов [20]. В ответ на объёмную нагрузку повышаются натрийуретические пептиды [21]. Что касается клинических проявлений ишемии -их меньше, чем при других пороках.…”
Section: компенсированная регургитацияunclassified
“…За один год примерно 8 % пациентов с МР достигают того состояния, когда требуется хирургическое вмешательство. И, поскольку есть такая ситуация, когда симптомы не распознаются, или игнорируются, весьма полезно исследование натрийуретическго пептида, который объективно зависит от преднагрузки, помогает принять тактическое решение [21]. Фракция выброса ЛЖ зависит от нагрузки, и зачастую переоценивается.…”
Section: диагностика при изменении симптомовunclassified